2016
DOI: 10.1111/codi.13245
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of perioperative nutrition within an Enhanced Recovery After Surgery programme for colorectal surgery: a qualitative study

Abstract: AimNutrition is an important element of the Enhanced Recovery After Surgery (ERAS) programme. Patients have previously indicated that nutrition is a key component of ERAS that requires improvement. Our aim was to explore the perioperative nutrition experiences of colorectal surgical patients to identify barriers and facilitators to the integration of nutrition within ERAS.MethodSixteen individuals undergoing colorectal surgery participated in a semi‐structured interview between postoperative day three and hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 36 publications
(56 reference statements)
6
66
0
6
Order By: Relevance
“…When the rationale for the ERAS element was not established, including proof of its effectiveness and safety, adherence was poor for both patients and providers—largely because the recipient was unconvinced or unmotivated to perform the task. Similar qualitative findings have been reported by Short et al, who concluded that the key patient barrier to adherence of perioperative nutrition protocols within a colorectal ERAS program was the poor provision of information. Likewise, a qualitative study by Laur et al identified that hospital staff need a reason, such as perceived or experienced benefits, to change their nutrition care practices.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When the rationale for the ERAS element was not established, including proof of its effectiveness and safety, adherence was poor for both patients and providers—largely because the recipient was unconvinced or unmotivated to perform the task. Similar qualitative findings have been reported by Short et al, who concluded that the key patient barrier to adherence of perioperative nutrition protocols within a colorectal ERAS program was the poor provision of information. Likewise, a qualitative study by Laur et al identified that hospital staff need a reason, such as perceived or experienced benefits, to change their nutrition care practices.…”
Section: Discussionsupporting
confidence: 86%
“…That is, coding and theme development are directed by the content of the data—referred to as bottom‐up , in which relevant food and nutrition codes were identified in the data (eg, “white bread”). An inductive, rather than deductive, approach was deemed appropriate for our work given the paucity of published research on the nutrition experiences of patients within an ERAS program setting. The analysis involved the following 6 steps: (1) familiarization with the data, (2) coding the data based on descriptive elements of the data or informed ideas in relation to the research question, (3) identifying potential themes from the codes and collating data under each theme, (4) reviewing and refining the themes (within and across the dataset), (5) defining and naming the themes, (6) contextualizing the analysis in relation to the existing literature and theories.…”
Section: Methodsmentioning
confidence: 99%
“…Weight loss in the perioperative period influences people's lives during recovery and post‐operative rehabilitation . Other researchers have highlighted that nutritional information is a priority for individuals and their families . In a recent study of body composition, only 5% of people with colorectal cancer were found to be cachexic based on measurements of fat‐free mass pre‐operatively, suggesting that weight loss is a treatable consequence of colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Especially patients experiencing postoperative complications feel vulnerable at home and prefer to have ready access to expert clinical advice [118]. For the patient's sense of security and health self-efficacy after (early) discharge, it is important to give patients clear and concise oral and written information on nutritional intake and symptom management at home [119]. Post-discharge home assistance by a nutritional support professional is important.…”
Section: Enhanced Recovery After Surgery Programmentioning
confidence: 99%